Acute Sinusitis Resulting in a Craniotomy: An Uncommon Complication of a Common Infection. (16th August 2012) - Price, Allison; Mohan, Arjun; Bush, Larry M.
Abstract : Acute bacterial sinusitis is a common infectious condition. Patients may initially present with an uncomplicated infection and later, despite appropriate initial antibiotic therapy, develop a potentially life-threatening complication. Interventions aimed at alleviating such unexpected events need be prompt and adequate. We describe a case of a patient who initially presented with signs and symptoms of acute sinusitis later to be diagnosed with a frontal epidural abscess.